3x - 1 = 2x
3x = 2x + 1
3x - 2x = 1
x = 1
Answer:
<em>5x² + 10x + 2 </em>
Step-by-step explanation:
g(x + 1) = 5(x + 1)² - 3 = 5( x² + 2x + 1 ) - 3 = <em>5x² + 10x + 2</em>
Answer:x^12
Step-by-step explanation:
Answer:
Step-by-step explanation:
y=a(x-0)(x-2)
=a(x^2-2x)
=a(x^2-2x+1-1)
or y=a(x-1)^2-a
(1,5) lies on it.
5=a(1-1)^2-a
5=0-a
or a=-5
so y=-5(x-1)^2+5
Answer:
m<EDA=35°
m<DAE=35 diagonal bisect it
Step-by-step explanation:
m<AED=180-2×35=110°(by sum of interior angle of the triangle)
m<BCE=mDAE=35° alternate angle